Aerial legacies of COVID-19 - Klauser, Francisco (My University, 2025)
Abstract. Based on examples taken from Switzerland, the paper offers an exploratory analysis of how the fight against COVID affected the societal relevance of the air, in its (1) elemental, (2) embodied, (3) affective, (4) socio-technical and (5) power-related dimensions. Together, these levels highlight the fact that the fight against COVID-19 increased the air's relevance as a focal point of societal concern and judgement and of competition and dispute, which in turn produced novel ways of ordering the air through legally, practically and materially defined geometries, internal structures, and contours. As the paper shows, these geometries of the air were and still are socio-politically produced in highly unequal ways. To date, they remain inherently pluralistic and as such fundamentally conflictual. The aerial legacies of COVID-19 are invested by various power relations that need critical attention. Over 150 years ago, the risks of waterborne diseases such as Cholera were tamed by the public provision of clean water. We argue that similar efforts are warranted to provide clean indoor air for all by removing the threats posed by airborne diseases such as COVID-19, influenza and tuberculosis … Our panel of scientific experts strongly recommends that the clean air needs of offices, schools, theaters, public buildings, and mass transportation systems be assessed and that measures be taken to ensure clean air in all indoor environments. (Expert group “Pandemic-proof buildings”, 2022:3) The preceding quote underscores the centrality of the issue of the air in the legacies of the fight against COVID-19. Aiming to perpetuate the lessons learnt from the respiratory disease, the quoted white paper asks for the development and implementation of a wide range of novel and/or improved air-related technological solutions whilst also suggesting, on a more general level, the establishment in Switzerland of a National Research Programme on “Clean air for pandemic-proof buildings” and the creation of an “Indoor air competence center” (Expert group “Pandemic-proof buildings”, 2022:4). The emerging post-pandemic policy agenda resonates with many other media-reported claims for long-term improvements of the indoor air quality in schools (Direction de la formation et des affaires culturelles, 2022; Eykelbosh, 2022), factories (Wirth, 2021), hospitals (Bourban, 2022) or trains (Monay, 2022). Also think of the ongoing debates about the wearing of face masks on public transport and other spaces of togetherness and micro-movements (Zhang and Zhai, 2022), and consider the discussions about the future usefulness of the materials deployed and lessons learnt from the access-control and social-distancing measures that created a patchwork of more or less hermetically enclosed and internally redesigned “bubbles of shared breathing” through which and in which movement was allowed to happen during the COVID years (Jubin, 2022; Lee and Eom, 2023). These examples reiterate the aerial sensitivity that remains from the fight against COVID-19. Thus if we are to understand and question the legacies of the fight against COVID-19, such is my basic argument, the question of the air must be placed centre stage. More specifically, based on examples taken from Switzerland, the paper offers an exploratory analysis of how the fight against COVID affected the societal relevance of the air, in its (1) elemental, (2) embodied, (3) affective, (4) socio-technical and (5) power-related dimensions. Together, these levels highlight that the fight against COVID-19 increased the air's relevance as a focal point of societal concern and judgement and of competition and dispute, which in turn produced novel ways of ordering the air through legally, practically and materially defined geometries, internal structures, and contours. As the paper shows, these geometries of the air were and still are socio-politically produced in highly unequal ways. To date, they remain inherently pluralistic and as such fundamentally conflictual. The aerial legacies of COVID-19 are invested by various power relations that need critical attention.